Intensity of competition and firm innovative behavior - O'Leary, Daragh; Doran, Justin; Power, Bernadette (Economics and Business Letters, 2022)
Using a novel self-reported measure competitive intensity and four distinct forms of innovation (product, process, marketing and organisational) from the European Commission Flash Eurobarometer 433 dataset, this paper comprehensively identifies the impact of competitive pressure on firm innovation for four broad sectors of the economy. A logit model by innovation type is used to estimate the impact of the intensity of competition on the firm’s decision to innovate. Firm reported intensity of competition is found to have a positive impact on product and market innovation. Significant heterogeneities exist in the impact of minor and major degrees of competition across innovation types and sectors supporting both Arrow’s (1962), and to a lesser degree Schumpeter’s (1943), perspectives on this relationship.